Peran Pendidikan Gerakan Pramuka Dalam Pembentukan Karakter Kepemimpinan Peserta Didik: Studi Kasus Di Madrasah Aliyah Negeri MAN 1 Kota Cilegon-Banten - arman munadi; Hartono Rudi (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2020)
Scout education is one of the non-formal education which is a place for the development of self-potential and has noble character, self-control, and life skills to give birth to the successors of the nation and state struggle. The process of character formation is an effort to help the mental development of children both physically and mentally. One non-formal education that can shape the character of leadership for students is extracurricular, especially scout education. The purpose of this research is to describe